The effects of fiscal and monetary policy on economic growth in Zambia - Luneta, Dean (School of Economics, 2025)
This study assesses the impact of fiscal and monetary policy on economic growth in Zambia for the period 2010Q1 to 2022Q4 using money supply and the monetary policy rate as monetary policy instruments and fiscal policy instruments such as government expenditure and fiscal policy outcomes in the form of government revenue. Government expenditures excluded interest payments from total expenditure as the data did not explicitly provide lines for government expenditure in the domestic economy. Government revenues were modelled as policy outcomes of fiscal policy to rule out the possibility of having to pinpoint the accurate form of tax tools or instruments such as the income tax rate, value-added tax rates, or rates associated with customs duty. This study uses vector autoregression (VAR) model to conduct the empirical analysis of the impact of monetary and fiscal policy on economic growth. Within the VAR framework, the Structural VAR (SVAR) was used to model the dynamic relationship among the different variables and trace out the impact of shocks from monetary and fiscal instruments using impulse response functions. The SVAR uses a recursive identification strategy and ordered the exogenous copper prices first, followed by GDP, inflation, a monetary policy instrument and a fiscal policy instrument. Consistent with theory, the results of the impulse response functions show that money supply positively affects GDP but also drives inflation up. On the other hand, the bank policy rate did not have a significant effect on GDP on its own but it seemed to slow down inflation. In the same vein, both government revenue and expenditure serving as fiscal instruments did positively affect GDP but also edged inflation upwards across the 20-period horizon.